WATER MANAGEMENT OF MIKOŁAJKI CITY AND COMMUNE - Filipkowska, Urszula; Janczukowicz, Wojciech; Karnicka, Barbara (Polish Journal of Natural Sciences, 2023)
The town and commune of Mikołajki, located in the Warmian-Masurian Voivodeship, have about 7,457 inhabitants. Over 83% of the commune's inhabitants are covered by the water supply network. The Mikołajki commune has four water intakes (one of which is out of use) and three water treatment plants. The water used by the inhabitants of the commune meets all sanitary requirements